Molecular analysis of the cyclin-dependent kinase inhibitor family: p16(CDKN2/MTS1/INK4A), p18(INK4C) and p27(Kip1) genes in neuroblastomas - Kawamata, Norihiko; Seriu, Taku; Koeffler, H. Phillip; Bartram, Claus R. (Cancer, 1996)
BACKGROUND Chromosomal abnormalities involving band 1p32, especially deletions, are frequent in neuroblastomas, indicating that a tumor suppressor gene(s) is localized at this region. The p18 gene, one of the cyclin-dependent kinase inhibitor (CDKI) genes, maps to this chromosomal region. Complexes of cyclin and cyclin-dependent kinase (CDK) play important roles in the cell cycle. CDKIs inhibit the kinase activities of these complexes and block transitions of the cell cycle. Some of the CDKI genes may be tumor suppressor genes. For example, the CDKI genes p16 and p15 are frequently deleted in various malignancies and are thought to contribute to cellular transformations. METHODS To elucidate the importance of CDKI genes, including the p18 as well as the p16 and p27 genes in tumorigenesis of neuroblastoma, 25 neuroblastomas were analyzed for deletions by Southern blot analysis and for point mutations by polymerase chain reaction-single strand conformational polymorphism. RESULTS No deletions, rearrangements, nor mutations were detected in these genes, however, polymorphisms reported previously were detected. CONCLUSIONS Abnormalities, including deletions and point mutations of the p16, p18, and p27 genes, were not observed in this series of neuroblastomas. Other mechanisms to inactivate these genes, such as transcriptional or translational defects, must be analyzed. CDKI genes rarely contributed to tumorigenesis in neuroblastomas. Cancer 1996;77:570-5.
Elektronische Reproduktion der Druck-Ausgabe 6. Dezember 1998
Gesehen am 08.01.2024